Metabolic patterns of bacterial communities in aerobic compost teas associated with potential biocontrol of soilborne plant diseases - PANE, Catello; CELANO, Giuseppe; ZACCARDELLI, Massimo (Phytopathologia Mediterranea, 2014)
Aerated compost teas (ACTs) are organic products obtained by forced aeration of composts suspended in liquid phase. These products may be biological control tools alternative to synthetic fungicides, because ACTs contain antagonistic microorganisms. In this study, soilborne disease suppressive ability of seven water ACTs, extracted from five horticultural residue-based composts, from an animal waste anaerobic solid digestate and from a commercial municipal waste compost, was assessed using in vitro and in vivo systems. All the ACTs inhibited in vitro growth of Verticillium dahliae, Fusarium oxysporum f. sp. lycopersici, Rhizoctonia solani, Sclerotinia minor, Sclerotium rolfsii and Botrytis cinerea. Filter or thermal sterilization eliminated in vitro suppression, suggesting that microorganisms play key roles in pathogen inhibition. Drenching applications of raw ACTs have potential to reduced disease symptoms caused by R. solani on savoy cabbage, S. minor on lettuce and S. rolfsii on pepper, improved the biomass production and did not show any sign of phytotoxicity. Both in vitro and in vivo suppressiveness of ACTs may be explained by antagonistic bacterial communities that provide general suppression activities. The metabolic BIOLOG GN and GP profiles reflected the functional potential of the numerically dominant members of the microbial communities used as inoculum. This study has demonstrated that useful resident microorganisms, including mainly Gram-positive and Gram-negative antagonistic bacteria, are likely to be responsible for biological control activity of ACTs.